2014
DOI: 10.4049/jimmunol.1302341
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Induction by SIRT6 through Attenuation of Insulin-like Growth Factor Signaling Is Involved in the Regulation of Human Bronchial Epithelial Cell Senescence

Abstract: Cigarette smoke (CS)–induced cellular senescence has been implicated in the pathogenesis of chronic obstructive pulmonary disease, and SIRT6, a histone deacetylase, antagonizes this senescence, presumably through the attenuation of insulin-like growth factor (IGF)-Akt signaling. Autophagy controls cellular senescence by eliminating damaged cellular components and is negatively regulated by IGF-Akt signaling through the mammalian target of rapamycin (mTOR). SIRT1, a representative sirtuin family, has been demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(159 citation statements)
references
References 45 publications
5
153
0
1
Order By: Relevance
“…8,25 Hence, we assumed that our findings of accumulations of fragmented mitochondria might result from insufficient mitophagy in the airway epithelial cells of COPD lung and also in CSE-exposed HBEC. 8,24,25 Supporting this notion, autophagy and mitophagy activation induced by Torin1 resulted in enhanced degradation of autophagosomal contents including mitochondrial debris and an increase in undamaged mitochondrial number as shown by EM, and also reduced CSE-induced accumulation of ubiquitinated proteins and SQSTM1 in the mitochondrial fraction of HBEC (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,25 Hence, we assumed that our findings of accumulations of fragmented mitochondria might result from insufficient mitophagy in the airway epithelial cells of COPD lung and also in CSE-exposed HBEC. 8,24,25 Supporting this notion, autophagy and mitophagy activation induced by Torin1 resulted in enhanced degradation of autophagosomal contents including mitochondrial debris and an increase in undamaged mitochondrial number as shown by EM, and also reduced CSE-induced accumulation of ubiquitinated proteins and SQSTM1 in the mitochondrial fraction of HBEC (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…23 In addition to accumulation of ubiquitinated proteins and SQSTM1 resulting from insufficient autophagic degradation, we have recently demonstrated an increase in fragmented mitochondria in the airway epithelial cells of COPD lung. 8,24,25 Furthermore, our in vitro experiments demonstrate that cigarette smoke extract (CSE)-induced accumulation of fragmented mitochondria is accompanied by increased mitochondrial ROS production and acceleration of human bronchial epithelial cell (HBEC) senescence. 24 Taken together, it is likely that insufficient mitophagic elimination is involved in the accumulation of fragmented mitochondria in response to CS exposure in COPD lung.…”
Section: Introductionmentioning
confidence: 99%
“…Besides direct interactions with FOXO3a, SIRT3 also has a potential indirect impact on FOXOs by moderating Akt overactivation by ROS [158]. SIRT6 has been shown to suppress IIS signalling-modulated genes [194], resulting in reduced FOXO1 expression [193]. SIRT6 also mediates p53-induced nuclear sequestration of FOXO1 in the regulation of energy metabolism [235].…”
Section: Transcriptional and Post-transcriptional Regulators As Sirtumentioning
confidence: 99%
“…Therefore, pathways associated with activation of SIRT1 and SIRT6 are an attractive approach for novel therapeutic targets for COPD. In the preclinical models efficacy of non-selective activators of SIRT1 using the pharmacological activator SRT1720 has been demonstrated Activation of SIRT1 via SRT2172 inhibits pulmonary neutrophil accumulation, and completely restored exercise tolerance and the fall in oxygen saturation and protects against cigarette smoke (CS) and elastase-induced emphysema in mice [32]. Furthermore, resveratrol, a substance shown to activate SIRT1 attenuates cigarette smoke extract (CSE)-mediated glutathione depletion through reversing CSE-mediated NRF2 carbonylation in lung epithelium cell line, A549 cells [31,32].…”
Section: Epigenetics Of Copdmentioning
confidence: 99%
“…In the preclinical models efficacy of non-selective activators of SIRT1 using the pharmacological activator SRT1720 has been demonstrated Activation of SIRT1 via SRT2172 inhibits pulmonary neutrophil accumulation, and completely restored exercise tolerance and the fall in oxygen saturation and protects against cigarette smoke (CS) and elastase-induced emphysema in mice [32]. Furthermore, resveratrol, a substance shown to activate SIRT1 attenuates cigarette smoke extract (CSE)-mediated glutathione depletion through reversing CSE-mediated NRF2 carbonylation in lung epithelium cell line, A549 cells [31,32]. Due to a recent study in human airway smooth muscle cells, resveratrol is suggested as an anti-inflammatory therapy alternative to corticosteroids in COPD, particularly in COPD exacerbations [33].…”
Section: Epigenetics Of Copdmentioning
confidence: 99%